PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. KARYA PRIMA BANGKIT - Lilah Karomi (Ekonis: Jurnal Ekonomi dan Bisnis, 2026)
This study aims to determine the Influence of Work Motivation and Work Environment on Employee Satisfaction of PT. Karya Prima Bangkit. The method used in this study is a quantitative method. The data collection technique is carried out through primary and secondary data, namely data obtained through questionnaires and studying documents related to the research. The research sample used a saturated sample, namely employees of PT. Karya Prima Bangkit which totals 85 employees. The analysis methods used in this study were multiple regression analysis with validity test, reliability test, normality test, multicoloniarity test, heteroskedesticity test and autocorrelation test, hypothesis testing using t-test and f test and determination coefficient analysis. The research results show that Work Motivation has a significant effect on Job Satisfaction, Work Environment has a significant effect on Job Satisfaction, and both Work Motivation and Work Environment simultaneously have a significant effect on Job Satisfaction.Keywords:  Work Motivation, Work Environment, Job Satisfaction.